Pengaruh Persepsi Harga, Kualitas Pelayanan, dan Kualitas Produk terhadap Keputusan Pembelian di Kopi Kenangan - Muhammad Raffi Ardisyahputra; Chatarina Yunita Tarigan (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Abstract: This study aims to analyze the influence of price perception, service quality, and product quality on consumer purchasing decisions on Kopi Kenangan products. The approach used in this study is quantitative with a survey method, which was carried out in the period from February to April 2025. A total of 100 respondents filled out a questionnaire distributed using the Accidental Sampling technique as a data collection method. The data collected were analyzed using linear multiple regression to determine the relationship between these variables. The results of the study indicate that partially, service quality and product quality have a significant effect on consumer purchasing decisions. Conversely, price perception does not have a significant effect individually. However, simultaneously the three variables are proven to have a significant effect on purchasing decisions on Kopi Kenangan products. This finding indicates the importance of service and product quality in influencing purchasing decisions, while price factors tend not to be the main consideration for consumers. This study provides input for Kopi Kenangan management to focus more on improving product and service quality in order to increase sales.